SOCCER PLAYERS VS MEDIA: THE EVOLUTION OF EXPOSURE OF ATHLETES (Fiep Bulletin - online, 2012)
This paper deals with the relation among journalists and football players, emphasizing the changes caused throughout the years. Press media and social networks were the stressed themes as they are part of the consequences of this evolution of communication. The objective is to demonstrate how these changes cause interference on the professional of communication's work and how the misuse of these tolls can be detrimental to the athletes and club image.The methods used for this research were bibliographic research and direct interview.
Keywords: Press Media; Social Networks; Journalism History